A New Inverse Lomax Weibull-G Family of Distributions with Applications - Falgore, Jamilu Yunusa; Abubakar, Yahaya; Doguwa, Sani Ibrahim; Mohammed, Aminu Suleiman; Imam, Abdussamad Tanko (Darul Yasin Al Sys, 2024)
The field of statistics is constantly evolving, and new approaches are being developed to model real-world datasets. Despite this, there are still many significant concerns surrounding real data that remain unresolved by existing approaches. One of the drawbacks of the Inverse Lomax distribution is that it belongs to the inverted family of distributions, which limits its application and makes it unsuitable for some situations. Based on these, a new family of distributions called Inverse Lomax Weibull G (ILWG) based on the Inverse Lomax-G and Weibull-G was proposed in this study. Some statistical properties of the family such as the quantile function, moments, and characteristic function were presented. Exponential distribution was used as a member of this family to demonstrate the applicability of the new family. Some statistical properties of the Inverse Lomax Weibull exponential distribution (ILWED) such as quantile function, moments, and characteristic function were demonstrated. ILWED's shapes can be right skewed and symmetric, as the case maybe. Sample quantiles were presented. A simulation study was also presented to explore the desirable properties of the ILWED. Lastly, an application to three (3) different datasets was demonstrated based on the ILWED.